MiRNA-221 is elevated in cystic fibrosis airway epithelial cells and regulates expression of ATF6 - Oglesby, Irene K.; Agrawal, Raman; Mall, Marcus A.; McElvaney, Noel G.; Greene, Catherine M. (Molecular and Cellular Pediatrics, 2015)
MicroRNA (miRNA) and messenger RNA (mRNA) expression differs in cystic fibrosis (CF) versus non-CF bronchial epithelium. Here, the role of miRNA in basal regulation of the transcription factor ATF6 was investigated in bronchial epithelial cells in vitro and in vivo.